EVIDENCE OF SUMMER NUTRITIONAL LIMITATIONS IN A NORTHEASTERN WASHINGTON MOOSE POPULATION - Cook, Rachel C.; Oyster, Jared; Mansfield, Kristin; Harris, Richard B. (Lakehead University, 2021)
Understanding the role of summer-autumn nutrition is critically important as moose (Alces alces) populations decline along their southern range in North America because it influences dynamics through performance and susceptibility to predation, disease, and parasitism. To assess nutritional limitations during summer-autumn, we estimated body fat and protein reserves (n = 61), pregnancy rate (n = 71), and lactation status (n = 59) of adult female moose in northeastern Washington State in December 2013, 2014, and 2016. Adult pregnancy rate was depressed (79%) and correlated with loin muscle thickness, and 14% of adult moose had evidence of delayed conception. Adult moose, particularly those that had successfully raised a calf, entered winter with low energy stores. Lactating moose were thinner than non-lactating moose and overall, 79% of moose sampled had < 9% body fat, indicating at least moderate nutritional limitations linked to performance and survival. Body fat was positively related to subsequent survival, and marrow fat levels indicative of starvation or severe nutritional stress were found in 56% of femurs (10 of 18) collected. Combined, these data highlight the importance of accounting for reproductive history when interpreting nutritional condition data and the importance of sampling moose populations in autumn when interpreting the influence of seasonal habitats on subsequent productivity and mortality.